The role of digital competence in improving service quality and employee performance - Kusni Ingsih; Sih D. Astuti; Fery Riyanto (SA Journal of Human Resource Management)
Orientation: Digital acceleration forces all public service organisations to prepare to shift from traditional methods to digital methods. Thus, this phenomenon challenges today’s public service organisations to present new service innovations with technological elements to create superior performance.